(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
The Tejgaon industrial area is located within the Dhaka Municipality area and about 5 km north of the city centre. At Tejgaon soil pH was around neutrality (mean 6.73) although the minimum value was 5.3 and the maximum 7.6. High buffering capacity resulting from high soil organic matter content (4.87-11.55%) probably influenced soil pH to a neutral value. Electrical conductivity (EC) (25-551 μS), organic matter (OM) (4.87-11.55%) and nitrogen (N) contents were also influenced by the industrial wastes and effluents of the factories. The average Pb concentrations (mg/kg) in different soil fractions were 7.80, 21.85, 56.15 and 130.29 and 11.42, 20.27, 40.33 and 95.08 in water-soluble, NH4OAc extractable, DTPA ( Dietheline-Triamine-Penta-Acetic acid) extractable and total fractions during dry (January) and rainy seasons (September) respectively. Comparing 1st (rainy season) and 2nd (dry season) sampling data, Pb concentrations in different soil fractions were higher in the 2nd sampling data. Concentration of total Pb in soils during 1st sampling were found above the natural background level with few exceptions. Only 4% of total Pb (=20 mg kg-1) samples were in the normal range during wet season. Lead concentration in the group of tolerable level was 58% (>20-<=100 mg kg-1) and 38% (>=100 mg kg-1) were found in the group of in excess of tolerable level during 1st sampling. On the other hand 62.5% (>=100 mg kg-1) were found in the group of in excess of tolerable level (0.01 mg kg-1 Pb) during dry season. In case of water samples, total Pb concentration in the rainy season, all samples were found in the group of in excess of tolerable level during 1st sampling. Plant samples were found to contain untolerable total Pb (>20 mg kg-1) during rainy and dry seasons, respectively. Key words: Speciation; Tejgaon soil; Industrial area; Lead. DOI: http://dx.doi.org/10.3329/bjsir.v46i3.9032 BJSIR 2011; 46(3): 277-290